Shifts in Polarity in the Post-war Global System - Attempted European Re-colonisation in Asia - Huntley, Matthew David (2017)
France and Britains failure in their attempt to re-colonise parts of South-East Asia after the Second World War came out of miscalculations made by their governments and their state institutions. The international system did not transition immediately after the war from multi-polarity to bipolarity. A window of opportunity was available for the two countries to regain influence in the region. The external political environment in the region was not unfavourable to a return of European colonial powers and there were no immediate viable challengers. Foreign policy misjudgements, weak domestic political systems and changes in priorities all contributed to the decline in influence of these two European colonial powers in South-East Asia. This thesis applies realist principles in combination with aspects of constructivism, while observing system and unit levels, to ascertain the root causes of the decline of British and French influence in the region.